EKSISTENSI MEDIA KOMUNIKASI: STUDI TENTANG SUMBANGSIHNYA TERHADAP PELAKSANAAN DAKWAH ISLAMIYAH - Hamiruddin, Hamiruddin (Al-Irsyad Al-Nafs : Jurnal Bimbingan dan Penyuluhan Islam, 2021)
Da'wah as one of the efforts to invite mankind to believe, live and practice Islamic teachings that in its operation require the existence of communication as a medium to transfer Islamic teachings so that islamic teachings can be believed and practiced by humans as the target of da'wah. The use of communication media in the implementation of da'wah is a demand for the progress of the times, because with the use of technological products in the field of information and communication can make the implementation of da'wah is organized in accordance with the demands of the times.